Using Quickwriting in Improving the Students’ Ability to Write Paragraph - Abdullah Syukur; Ardhy Supraba (LETS: Journal of Linguistics and English Teaching Studies, 2020)
The objectives of this research were to find out: the ability of the second semester students of Informatics Study Program at Cokroaminoto Palopo University in writing paragraph through quickwriting. This research employed quantitative method. The method used in this research was pre-experimental with one group pretest-posttest design. The istrument was writing test. The results of the research shows that quickwriting is effective to be used to improve students’ ability in writing because there was a significant difference between the progresses in writing of the students who were studying through quickwriting and those are not. By quickwriting strategy, the students can express their ideas easily without stopping and rushing. It gave them writing power and easy to understand. No more stopping in writing because it’s under the pressure of time, and the students’ attitude of the second semester students of Informatics Study Program Cokroaminoto Palopo University in learning English writing was positive and more interested in learning English writing through quickwriting strategy. It was proved that there was significant difference between the result of students’ pre-test and post-test by the value of t-test (12.50) is greater than the value of t-table (2.011).